Correlation evaluation between cancer microenvironment related genes and prognosis based on intelligent medical internet of things - Ren, Shoulei; Cao, Wenli; Ma, Jianzeng; Li, Hongchun; Xia, Yutao; Zhao, Jianwen (Frontiers in Genetics, 2023)
Tumor Microenvironment (TME) has been intensively studied at present. Scientists are committed to analyzing the relationship between TME and human health, so as to seek opportunities for curing cancer patients. However, there is no in-depth analysis on the correlation between cancer TME related genes and prognosis. Although the development of Internet of Things (IoT) technology brings more possibilities to the research in this field, there are still deficiencies in the research in this field. In order to change this situation, this paper used the intelligent medical IoT to analyze cancer TME related genes. It designed experiments to analyze cancer related genes and drew conclusions. In cervical cancer, the life cycle of patients with high expression of P16 gene was prolonged compared with low expression, and the survival rate remained at 35%.